Aplastic anemia with paroxysmal nocturnal hemoglobinuria clones at diagnosis: Overlap, challenges, and therapeutic dilemmas - Sirajwala, Abulkalam Atiqurrehman; Raval , Rajvi Dinesh; Patel , Rahenuma Yusuf; Bodar, Deven Atul (Indian Journal of Case Reports, 2026)
Aplastic anemia (AA) is a rare, potentially life-threatening bone marrow failure syndrome characterized by pancytopenia and hypocellular marrow. Clonal evolution, particularly the coexistence of paroxysmal nocturnal hemoglobinuria (PNH) clones, has important diagnostic and prognostic implications. We report the case of a 25-year-old male who presented with recurrent mucosal bleeding, progressive fatigue, exertional dyspnea, weight loss, and fever. Initial evaluation revealed severe pancytopenia with reticulocytopenia and markedly hypocellular bone marrow showing aplasia. Flow cytometry demonstrated PNH clones within red cells (0.03%), granulocytes (8.35%), and monocytes (6.45%). The absence of hemolysis, elevated lactate dehydrogenase, or thrombosis supported AA as the primary disease. The patient was managed with transfusion support, antifibrinolytics, and was listed for hematopoietic stem cell transplantation. The coexistence of PNH clones in AA complicates diagnosis due to overlapping clinical features but also carries prognostic implications. Small PNH clones are increasingly detected with high-sensitivity fluorescent labeled aerolysin-based flow cytometry and may predict a favorable response to immunosuppressive therapy. However, clonal expansion over time can lead to classical PNH with hemolysis and thrombosis, underscoring the need for serial monitoring. This case highlights the importance of routine PNH clone screening in AA patients at diagnosis. Even small, asymptomatic clones can influence prognosis and necessitate long-term surveillance.